Company law and sustainability : legal barriers and opportunities - Sjafjell, Beate; Richardson, Benjamin J. (Cambridge, UK : Cambridge University Press, 2015)
'This investigation of the barriers to and opportunities for promoting environmental sustainability in company law provides an in-depth comparative analysis of company law regimes across the world. The social norm of shareholder primacy is the greatest barrier preventing progress, and it also helps explain why voluntary action by companies and investors is insufficient. By deconstructing the myth that shareholder primacy has a legal basis and challenging the economic postulates on which mainstream corporate governance debate is based, Company Law and Sustainability reveals a surprisingly large unexplored potential within current company law regimes for companies to reorient themselves towards sustainability. It also suggests possible methods of reforming the existing legal infrastructure for companies and provides an important contribution to the broader debate on how to achieve sustainability'--
'This investigation of the barriers to and opportunities for promoting environmental sustainability in company law provides an in-depth comparative analysis of company law regimes across the world. The social norm of shareholder primacy is the greatest barrier to progress, and it also helps explain why voluntary action by companies and investors alone is insufficient. By deconstructing the myth that shareholder primacy has a legal basis and challenging the economic postulates on which the mainstream corporate governance debate is based, Company Law and Sustainability reveals the surprisingly large unexplored potential in current company law regimes for companies to reorient themselves towards sustainability. It also suggests possible methods of reforming the existing legal infrastructure for companies and makes an important contribution to the wider debate on how to achieve sustainability'--
Machine generated contents note: 1. Capitalism, the sustainability crisis and the limitations of current business governance Benjamin J. Richardson and Beate Sjafjell; 2. Corporate social responsibility and environmental sustainability David Millon; 3. Shareholder primacy: the main barrier to sustainable companies Beate Sjafjell, Andrew Johnston, Linn Anker-Sorensen and David Millon; 4. The role of board directors in promoting environmental sustainability Blanaid Clarke; 5. Accounting, auditing and reporting: supporting or obstructing the sustainable companies objective? Charlotte Villiers and Jukka Mahonen; 6. Financial markets and socially responsible investing Benjamin J. Richardson; 7. Limits to corporate reform and alternative legal structures Carol Liao; 8. The future for company law and sustainability Beate Sjafjell and Benjamin J. Richardson.
Includes bibliographical references and index.
Keywords: Corporate governance -- Law and legislation; Sustainable development -- Law and legislation; Corporation law